2013
DOI: 10.1016/s1001-0742(12)60252-6
|View full text |Cite
|
Sign up to set email alerts
|

The ex vivo and in vivo biological performances of graphene oxide and the impact of surfactant on graphene oxide's biocompatibility

Abstract: Graphene oxide (GO) displays promising properties for biomedical applications including drug delivery and cancer therapeutics. However, GO exposure also raises safety concerns such as potential side effects on health. Here, the biological effects of GO suspended in phosphate buffered saline (PBS) with or without 1% nonionic surfactant Tween 80 were investigated. Based on the ex vivo experiments, Tween 80 significantly affected the interaction between GO and peripheral blood from mice. GO suspension in PBS tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 36 publications
4
35
1
Order By: Relevance
“…Considerable thrombus formation could be induced by intravenously injected GO, indicating that this method of exposure is not applicable for repeated administration of GO in evaluating its death-inducing effect on blood cells [18,31]. Thus, in the current study, intraperitoneal injection was selected for GO treatment in mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considerable thrombus formation could be induced by intravenously injected GO, indicating that this method of exposure is not applicable for repeated administration of GO in evaluating its death-inducing effect on blood cells [18,31]. Thus, in the current study, intraperitoneal injection was selected for GO treatment in mice.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of the fluorescence spectrum indicated that the maximum emission wavelength for QDs used here was around 605 nm, indicative of red light. GO was synthesized using the Hummers method with minor revisions as previously described [18]. The size of GO was 300 to 1,000 nm, and the thickness was approximately 1 nm [18].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[334] In vitro, GO can provoke blood cell aggregation. [335] Mukherjee et al observed that GO and reduced GO induce pro-angiogenic activity [336] . GO and reduced GO could generate intracellular reactive oxygen species (ROS), which can influence the phosphorylation of Akt and active the NO signaling, thus finally triggered angiogenesis.…”
Section: Theranostic Nanomaterialsmentioning
confidence: 99%